Nutritional status, intestinal parasite infection and allergy among school children in Northwest Ethiopia - Amare Bemnet; Ali Jemal; Moges Beyene; Yismaw Gizachew; Belyhun Yeshambel; Gebretsadik Simon; Woldeyohannes Desalegn; Tafess Ketema; Abate Ebba; Endris Mengistu; Tegabu Desalegn; Mulu Andargachew; et al. (BMC, 2013)
Abstract Background Parasitic infections have been shown to have deleterious effects on host nutritional status. In addition, although helmintic infection can modulate the host inflammatory response directed against the parasite, a causal association between helminths and allergy remains uncertain. The present study was therefore designed to evaluate the relationship between nutritional status, parasite infection and prevalence of allergy among school children. Methods A cross sectional study was performed involving school children in two elementary schools in Gondar, Ethiopia. Nutritional status of these children was determined using anthropometric parameters (weight-for-age, height-for-age and BMI-for-age). Epi-Info software was used to calculate z-scores. Stool samples were examined using standard parasitological procedures. The serum IgE levels were quantified by total IgE ELISA kit following the manufacturer's instruction. Result A total of 405 children (with mean age of 12.09.1 ± 2.54 years) completed a self-administered allergy questionnaire and provided stool samples for analysis. Overall prevalence of underweight, stunting and thinness/wasting was 15.1%, 25.2%, 8.9%, respectively. Of the total, 22.7% were found to be positive for intestinal parasites. The most prevalent intestinal parasite detected was Ascaris lumbricoides (31/405, 7.6%). There was no statistically significant association between prevalence of malnutrition and the prevalence of parasitic infections. Median total serum IgE level was 344 IU/ml (IQR 117-2076, n = 80) and 610 IU/ml (143-1833, n = 20), respectively, in children without and with intestinal parasite infection (Z = −0.198, P > 0.8). The prevalence of self reported allergy among the subset was 8%. IgE concentration was not associated either with the presence of parasitic infection or history of allergy. Conclusion The prevalence of malnutrition, intestinal parasitism and allergy was not negligible in this population. In addition, there was no significant association between the prevalence of allergy and their nutritional status, and parasite infection. Further research prospective observational and intervention studies are required to address the question of causality between nutritional factors, parasites, and allergy.